Study on the Effect of Polysulfide Content on the Micromorphology and Spontaneous Combustion Characteristics of Coal - Hai-Fei Yao (Advances in Civil Engineering)
This paper aimed to study the effect of the polysulfide content on the micromorphology and spontaneous combustion characteristics of coal, in order to develop more targeted prevention and treatment strategies. To this end, this study selected the method of mixing different sulfides with very low sulfur content raw coal to prepare the coal samples to be tested. Various parameters, such as true density, porosity, micromorphology, and oxygen uptake of the different sulfur samples, were tested. The results reveal that sulfide had a certain expansion effect on the coal body and improved the pore structure of coal, and the porosity increased with the increase of the sulfur content. After adding iron (II) disulfide (FeS2) and iron (II) sulfide (FeS) powder to the original coal sample, the number of fine particles on the surface increased significantly. After increasing the oxidation temperature, the lamellar structure disintegrated, and the massive coal body was broken into several fine particles, which promoted the spontaneous combustion of coal. Polysulfide promotes the low-temperature oxygen absorption of coal and shortens the natural firing period of coal. FeS has a slightly greater effect on increasing the tendency of coal to spontaneously combust and shortening the shortest natural firing period of coal. Before the addition of FeS2 and FeS to the coal samples, the coal production amount was not much different below 80–90°C, and then, the gap gradually widened. Under the same temperature condition of coal, carbon monoxide (CO) production basically occurred first as the sulfur content increased. When FeS2 and FeS were added, the sulfur content of the coal samples was 3 and 4%, respectively, and the production of CO and ethene (C2H4) was the largest. Although the peak areas of aliphatic hydrocarbon, aromatic hydrocarbon, hydroxyl group, and carbonyl group in the coal samples with FeS were different, they all reached their maximum value when the sulfur content was 4%.